Extending the range of constant strain rate nanoindentation testing. Issue 4 (28th February 2020) - Merle, Benoit; Higgins, Wesley H.; Pharr, George M.
Abstract: Abstract : Constant strain rate nanoindentation hardness measurements at high sustained strain rates cannot be made in conventional nanoindentation testing systems using the commonly employed continuous stiffness measurement technique (CSM) because of the "plasticity error" recently reported by Merle et al. [ Acta Mater. 134, 167 (2017)]. To circumvent this problem, here we explore an alternative testing and analysis procedure based on quasi-static loading and an independent knowledge of the Young's modulus, which is easily obtained by standard nanoindentation testing. In theory, the method applies to any indentation strain rate, but in practice, an upper limit on the rate arises from hardware limitations in the testing system. The new methodology is developed and applied to measurements made with an iMicro nanoindenter (KLA, Inc.), in which strain rates up to 100 s −1 were successfully achieved. The origins of the hardware limitations are documented and discussed.